PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK TABUNGAN NEGARA (Persero) SYARIAH CABANG KOTA MEDAN - Mitha Sari Dewi; Erlyanti Erlyanti; Dewi Sundari Tanjung (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This research aims to determine the effect of the work environment and work motivation on employee performance at PT. Bank Tabungan Negara (Persero) in Medan City. The objectives to be achieved in this study are: 1) To determine the impact of the work environment on employee performance at PT. Bank Tabungan Negara (Persero) Syariah in Medan City, 2) To determine the work motivation of employees at PT. Bank Tabungan Negara (Persero) Syariah in Medan City. The research method used is the quantitative method. The population in this study is the employees of PT. Bank Tabungan Negara (Persero) Syariah Kota Medan. The determination of the research sample uses the saturated sampling technique, where the sample is the entire population. The sample in this study consists of 35 respondents. The data collection instrument used was a questionnaire. The independent variables are the work environment and work motivation, while the dependent variable is employee performance at PT. Bank Tabungan Negara PT. Persero (Syariah) Medan City. The data analysis technique uses classical assumption tests, multiple linear regression tests, and t-tests. The results of this study indicate that: 1) Partially, the work environment does not have a positive and significant effect on employee performance 2) Partially, work motivation has a positive and significant effect on employee performance. The implication of this research is the presence of cleanliness and good workplace environment observers to ensure that the tasks assigned to employees are carried out well, and it is expected that with the presence of work motivation, employee morale within an organization will improve.